INNOVATION IN POLICING REGARDING EU MEMBERSHIP IN TURKEY: POLICE OFFICERS’ PERCEPTIONS OF COMMUNITY POLICING - AKSOY, MURAT (2011)
ABSTRACT Innovations in Policing regarding EU Membership in Turkey: Police Officers’ Perceptions of Community Policing by Murat Aksoy The Turkish National Police (TNP) has been undergoing continuous reform and reorganization for over a decade, with many new departments and training facilities being set up. As part of this continuous change, a number of innovative initiatives, including community policing, have been introduced in Turkey in the past decade in anticipation of European Union membership. The advent of Community Policing (COP) was announced to the Police Organization, in a circular, by the Turkish Interior Ministry in 2005. In support of this new policy style, studies were also undertaken to run an EU sponsored project titled ‘Community Involvement in Suppression of Crimes’. It is expected that such policies and programmes will contribute to the approach to policing in Turkey. Similar to any other innovative initiative, effective implementation of COP as an innovative style depends on the police officers’ perceptions and acceptance in particular and the police organisation in general. However, to date, no empirical studies have been conducted to examine officers’ perceptions of community policing nationwide. The aim of this study, therefore, is to examine the perceived effectiveness of COP at the individual level through the expressed perceptions of participating police officers. In addition, this study also aims to identify the selected demographic and experiential variables, which determine the level of effectiveness of COP from the viewpoint of the police officers on the ground. In order to fulfil these aims, this study is constructed as an explorative case study for which primary data is collected through a questionnaire survey administered with 290 law enforcement community police officers from 16 cities across Turkey. Statistical methods are employed to analyse the primary data. The findings from the OLS regression analysis demonstrate that COP has the potential to be implemented in Turkey. After creating dependent and one independent variable using factor analysis, the results reveals that COP officers strongly support the program and they have positive perceptions of it. In addition, the majority of the participating COP officers are in support of the EU process to help the changing environment in Turkey, particularly in the Police service. The OLS model I identifies six variables with a statistically significant relationship. These variables are: ‘European Union’, ‘fear of crime’, ‘years of experience’, ‘volunteer or assigned’, ‘education’ and ‘proportion of COP to traditional policing’. The OLS model II reveals that there is a significant relationship in city size (population). In addition, the Black Sea, East Anatolia, and Aegean regions are statistically associated with the effectiveness of COP which means there are no differences according to region in Turkey. The findings of the study also rendered useful information for future developments. It can be concluded that the findings of this study can be expected to help practitioners, policymakers, and researchers for the development of future policies in the field